The Economic Impact of the High-Speed Train on Urban Regions - Peter M.J. Pol (European Regional Science Association (ERSA), 2003)
The impact of new transport systems depends on the spatial behaviour of urban actors. Connection to the High-Speed Train (HST)-network implies a reduction of the generalised transportation costs and thus an extension of the maximum acceptable transportation distances of actors. Individuals can either travel further or reach their destinations earlier; it means that their relevant region has become larger. With more welfare elements available within their relevant region, their welfare potential will increase. To improve their competitive edge in a service and information economy, cities have to have high grade (international) facilities, and to be attractive and well accessible. To achieve this, the urban actors involved have to strive for several kinds of balance. The advent of the HST can contribute to achieving these balances. It can inter alia play an important role in improving simultaneously the quality of urban life and the accessibility of city centres, and stimulating the development of diversified districts. The HST-connection can have a catalysing effect on a regional economy (it draws new activities and thus causes a region's economy to grow), or a facilitating effect (the new infrastructure will accommodate economic growth that is already in progress in an urban region). The advent of the HST can be beneficial to those cities that already hold a strong competitive position. They normally already have a relatively high economic potential and attractive location factors for new service companies and well-educated residents. Both these advantages will be further enhanced by the improving external accessibility. In weaker urban regions, the advent of the HST can be an opportunity to improve their competitive position and to obtain a higher position in the European urban hierarchy. The improving external accessibility may help to enhance their economic potential and location factors. However, a precondition for economic growth and renewal for these cities will be that this economic potential exceeds a certain critical (sometimes psychological) level. When it does not, the improved external accessibility may also lead to backwash effects (for instance, companies moving out of the urban region concerned, since their local markets will no longer be protected by transport barriers). Therefore, the advent of the HST is likely to particularly stimulate these weaker regions to improve their economic attractiveness.
Keywords: 330